Gene editing of human embryos is not contrary to human rights law: A reply to Drabiak - Boggio, Andrea ca. 20./21. Jh. (Bioethics, 2021)
In an article in this journal, Katherine Drabiak argues that green lighting genome editing of human embryos is contrary to “fundamental human rights law.” According to the author, genome editing of human embryos violates what we should recognize as a fundamental human right to inherit a genome without deliberate manipulation. In this reply article, we assess Drabiak's legal analysis and show methodological and substantive flaws. Methodologically, her analysis omits the key international legal instruments that form the so-called International Bill of Rights and thus fails to provide a full and accurate account of the fundamental international human rights standards. Substantively, Drabiak invokes, as a basis for prohibiting gene editing of human embryos, a legal standard (the rights and integrity of the future child) that is unknown to international law. Contrary to Drabiak's account, genome editing of human embryos is not prohibited under international law. Indeed, the right to health and the right to benefit from scientific progress may be interpreted as the basis of a legal duty to provide equality of access to germline gene editing, once determined it is beneficial and safe to use.